EP197/#293 Endometrial cancer recurrences in the era of COVID. (4th December 2022) - Patterson, Jenna; Riedinger, Courtney; Backes, Floor; O'Malley, David; Bixel, Kristin; Copeland, Larry; Cohn, David; Goodfellow, Paul; Cosgrove, Casey
Abstract : Objectives: Endometrial cancer (EC) is the most common gynecologic malignancy and surveillance includes symptom assessment and physical examination. During the COVID pandemic, access to care was limited and telemedicine was frequently utilized. Our objective was to evaluate the effects of the pandemic on the presentation and diagnosis of EC recurrence. Methods: A retrospective review of women with EC recurrence diagnosis between January 2015 and December 2021 was performed. Clinicopathologic data about presentation and diagnosis of recurrence was collected from the electronic health record. The first COVID case in Ohio was reported March 2020 and recurrence diagnosis after this date was considered 'after COVID.' Statistical analysis was performed using JMP Statistical Software. Results: During the timeframe, 201 patients were diagnosed with recurrent EC; 135 (67.2%) prior to COVID and 66 (32.8%) after COVID. There was no difference in the average time (in months) from diagnosis to EC recurrence (14.78 vs 17.64, p= 0.212) prior to or after COVID. The majority of EC recurrences were symptomatic (60.0% vs 59.1%, p=0.902) and nonlocalized in both groups (71.1% vs 74.2%, p=0.641). Most recurrences were diagnosed by oncologic providers (63.0% vs 66.7%, p=0.517). Lastly, no difference in the percentage of patients receiving treatment (82.2% vs 83.3%, p= 0.845) nor the follow-up compliance rate (88.2% vs 95.5%, p=0.102) between the two groups was detected ( table 1 ). Conclusions: Clinicopathologic presentation of EC recurrence did not change in our population after COVID. This suggests that health care adaptations utilized during the pandemic, including telemedicine, warrant further investigation.